Intelligent Flood Monitoring System Using IoT and Real-Time Notifications - Shafira Febriani; Muhamad Aziz Arrozaq; Rivaldo Nugraha; Anggi Cipta Lestari (Jurnal Informasi, Sains dan Teknologi, 2025)
Flood is a frequent natural disaster in Indonesia, often exacerbated by delays in information delivery from conventional manual monitoring systems. This study aims to design and build an automatic flood early warning system based on the Internet of Things (IoT) integrated with a web dashboard and WhatsApp notifications. The system utilizes the ESP32 microcontroller and MaxBotix MB7389 ultrasonic sensor for real-time water level data acquisition. The Research and Development (R&D) method was employed, focusing on device accuracy validation and system integration. The measured data is transmitted to a .NET-based server and stored in a PostgreSQL database. Results indicate that the system functions according to design. Sensor accuracy testing demonstrated a high degree of precision (99.12% - 100%) compared to manual measurements. Furthermore, the system successfully sends timely warning notifications via WhatsApp when water levels exceed predefined thresholds, providing a more effective solution than manual monitoring to enhance community preparedness.